2023
DOI: 10.3390/land12112013
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Urban Sprawl and Ecological Quality Study Case: Chiba Prefecture, Japan

Ruth Mevianna Aurora,
Katsunori Furuya

Abstract: The Japanese City Planning Act aims to control urban sprawl and promote compact urban development. Despite Japan’s aging population, urban sprawl remains a concern in shrinking sprawl situations. This impacts ecosystem services owing to the loss of natural areas. Ecological quality is regarded as a basic parameter for preventing urban sprawl. This study examined urban sprawl, ecological quality, and their relationship in Chiba Prefecture within the spatial context of the metropolitan region. Utilizing Shannon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that higher urban compactness, characterized by denser populations and more efficient land use, correlates with lower per capita GHG emissions [7][8][9][10][11][12][13][14][15][16]. This is often attributed to reduced vehicle usage in densely populated urban areas, where proximity to public facilities and efficient public transport systems diminish reliance on personal vehicles [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that higher urban compactness, characterized by denser populations and more efficient land use, correlates with lower per capita GHG emissions [7][8][9][10][11][12][13][14][15][16]. This is often attributed to reduced vehicle usage in densely populated urban areas, where proximity to public facilities and efficient public transport systems diminish reliance on personal vehicles [17][18][19].…”
Section: Introductionmentioning
confidence: 99%